(untitled) (Analytical Methods for Drug Development, 2025)
Author Dr. Ceema Mathew Professor, Dept of Pharmaceutical Analysis, Gokaraju Rangaraju College of Pharmacy, Bachupally, Hyderabad, Telangana, India Abstract Stability testing determines how drug quality changes over time under various environmental conditions. ICH guidelines define accelerated, intermediate, and long-term testing protocols across different climatic zones and container closure systems. Forced degradation studies employ acid/base hydrolysis, oxidation, photolysis, and thermal stress to identify degradation pathways, establish degradation product profiles, and develop stability-indicating methods. These studies generate samples containing degradation products at detectable levels, creating worst-case scenarios for method development. Stability-indicating methods separate and quantify degradation products with demonstrated specificity under stress conditions. Data interpretation applies trend analysis, shelf-life determination, and statistical approaches including regression analysis and tolerance intervals. Stability protocols integrate with product development from early formulation screening through post-approval changes, creating specifications for storage conditions, retest periods, and shelf-life claims. Keywords: Forced Degradation, Stability-Indicating Methods, Shelf-Life, Degradation Products, Photostability VIEW PDF